PERFOMACE COMPARISON BETWEEN FUZZY LOGIC CONTROLLERS AND HEDGE ALGEBRAS – BASED CONTROLLER FOR FURNACE - Duy, Nguyễn Tiến; Lân, Vũ Như (Vietnam Journal of Science and Technology, 2012)
SUMMARY In this paper, two controllers such as FLC (Fuzzy Logic Controller) and HAC (Hedge Algebras – Based Controller) are simulated in MATLAB SIMULINK. All the successfully designed controllers were compared. The responses of each controller were plotted in one window to verify the performance of each control algorithm. Simulation study has been done in MATLAB SIMULINK shows that the new controller – HAC produced better response and better performance compared to FLC strategies for controlling the temperature plant.